The ethical dilemma in Towards the swamp, by Gerardo Laveaga - Rodríguez Cruz, Indra Naivi (2024)
Hacia el Pantano is a novel written by Gerardo Laveaga, narrated in-médias-rrés, which raises a current 21st century issue: the ethical dilemma between what is right and what is expedient. Throughout the novel, we observe three intertwined stories where the characters experience a power struggle and a constant analysis in which they question whether their actions are based on their values and ideals or, on the contrary, whether their actions seek to favour third parties and are thus betraying themselves. The reader can analyse the context and discover the way in which the characters behave, and even feel empathy for them, as the author raises how normalised it is to be corrupt or corruptible in our society. Laveaga describes a complicated panorama and invites us to transform our beliefs and analyse our actions, which are sometimes clouded by the dishonesty that makes us accomplices of injustice.